THE EFFECT OF TAX MORALITY, TAX CULTURE, AND GOOD GOVERNANCE TO TAXPAYERS COMPLIANCE - Indar Khaerunnisa; Adi Wiratno; Elvira Luthan (The Accounting Journal of Binaniaga, 2016)
This study aims to determine how the effect of the tax morality of the level of participation of citizens, the confidence level, the level of local autonomy, national pride, demographic factors, economic conditions, deterrence factors, and the tax system to tax compliance. how cultural influences taxes consist of the respondents to react to the tax culture is a relationship between the tax authorities and the taxpayer, tax regulations and the national culture of tax compliance. how the influence of good governance such as human resources, information technology, organizational structure, processes and procedures as well as financial resources and incentives for tax compliance of corporate entities registered in the National Construction Contractors Association of Indonesia. Data obtained by sending a questionnaire to the members of the Bogor City GAPENSI 80 respondents with data analysis using Partial Least Square (PLS). Hypothesis testing results show that the path coefficient relationship between tax morality of compliance of tax of 0.3655 and the value of t-statistic of 3.0149 (> 1.96), testing hypotheses for testing the path coefficient relationship between culture variable tax on tax compliance at 0.2352 and the value of t-statistic of 2.1832 (>1.96), and the third hypothesis testing path coefficient value of the relationship between good governance on tax compliance by 0.2983 with a t-statistic values of 2.5984 (>1.96). Keywords: Tax Morality,Tax Culture, Good Governance, Compliance of Taxpayer